Negotiation readings, exercises, and cases - Lewicki, Roy J.; Saunders, David M.; Minton, John W. 1946- (Irwin/McGraw-Hill, 1999)
Explores the major concepts and theories of the psychology of bargaining and negotiation. This book also looks at the dynamics of interpersonal and intergroup conflict and its resolution.